2014
DOI: 10.1371/journal.pone.0105677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Vitamin A on Reproductive Performance and Immune Response of Broiler Breeders

Abstract: The effects of dietary vitamin A supplementation on reproductive performance, liver function, fat-soluble vitamin retention, and immune response were studied in laying broiler breeders. In the first phase of the experiment, 1,120 Ross-308 broiler breeder hens were fed a diet of corn and soybean meal supplemented with 5,000 to 35,000 IU/kg vitamin A (retinyl acetate) for 20 weeks. In the second phase, 384 Ross-308 broiler breeder hens were fed the same diet supplemented with 5,000 to 135,000 IU/kg vitamin A (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Vitamins can act on offspring through eggs, so we studied the effect of dietary vitamin A (VA) supplementation in maternal and their offspring on the intestinal tissue morphology and immune performance of goslings.VA can change the intestinal morphology and structure of animals [1]. VA can improve fecundity [2] and can promote the formation of sex hormones to maintain normal bone growth and development [3][4][5]. VA can also regulate the metabolism of fat, carbohydrates and proteins, promote growth, and play important roles in immune function and nonspecific responses to disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins can act on offspring through eggs, so we studied the effect of dietary vitamin A (VA) supplementation in maternal and their offspring on the intestinal tissue morphology and immune performance of goslings.VA can change the intestinal morphology and structure of animals [1]. VA can improve fecundity [2] and can promote the formation of sex hormones to maintain normal bone growth and development [3][4][5]. VA can also regulate the metabolism of fat, carbohydrates and proteins, promote growth, and play important roles in immune function and nonspecific responses to disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A and vitamin E are essential micronutrients throughout the life cycle and have many effects with antioxidant activities, recommended for chickens (NRC, 1994;Yuan et al, 2014). But, in this study, we can say that using P. major extract have no effect on serum vitamin A and E levels.…”
Section: Indian Journal Of Animal Researchmentioning
confidence: 59%
“…This trial described the effect of a nine weeks period of dietary supplementation with supra-nutritional levels of vitamin A and E in broiler breeders during the late production cycle, when fertility traits tend to decline. Both vitamins A and E are considered important factors related to the maintenance of fertility in mammals as well as in birds [11,23,32,33]. At the beginning of the experiment, hens in all groups showed similar laying ability even though the number of produced eggs was smaller than those proposed by Aviagen [34] for performance objectives of Ross-308 breeders (≤2 eggs/bird/week for the majority of the experimental groups vs. 3.60 eggs/bird/week for birds aged of 61 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely to a previous study showing that dietary supplementation of laying hens with levels of vitamin A above the National Research Council [36] recommendations had no effect on egg production [37,38], our study showed that it was possible to maintain or improve the egg production of hens under standard rearing conditions. Moreover, Yuan et al [23] failed to find any beneficial effect in using high levels of vitamin A in diet on the reproductive performance of broiler breeder hens. However, it is worth remembering that the mentioned previous studies used longer periods of supplementation covering the entire laying period, whilst in the current study were used hens at the end of the production phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation